2010
DOI: 10.1111/j.1439-0450.1977.tb01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Susceptibility of Rabbits, Rats, Mice and Pigs to Infection with Aujeszky Disease Virus (ADV) in the Development of an Efficacy Test for ADV Vaccines

Abstract: Summary The results of Aujeszky virus titrations in rabbits, rats, mice and pigs show that rabbits are apparently the most susceptible animals. Zusammenfassung Vergleich der Empfindlichkeit von Kaninchen, Ratten, Mäusen und Schweinen gegen eine Infektion mit Aujeszkyschem Virus Nach vergleichenden Titrationen von Aujeszkyschem Virus in Kaninchen, Ratten, Mäusen und Schweinen hat sich gezeigt, daß Kaninchen gegen das Aujeszkysche Virus am empfindlichsten sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, 33.3% (2/6) of the pigs did not develop a protective level of antibodies, indicating that pigs need to be administered the virus twice or more. It has been reported that the oral route required more Aujeszky diseases virus vaccine than the intranasal route [ 22 ]. Additionally, the presence of antibodies against RABV has been confirmed in wild boar living in Slovenia where anti-rabies vaccination occurred in 2005-2006 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, 33.3% (2/6) of the pigs did not develop a protective level of antibodies, indicating that pigs need to be administered the virus twice or more. It has been reported that the oral route required more Aujeszky diseases virus vaccine than the intranasal route [ 22 ]. Additionally, the presence of antibodies against RABV has been confirmed in wild boar living in Slovenia where anti-rabies vaccination occurred in 2005-2006 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pigs vaccinated three times attained 100% seropositivity earlier (by 7 weeks after vaccination) than did pigs vaccinated twice. It was earlier reported that large quantities of ADV were necessary to adequately infect animals and that the oral route required more vaccine than did the intranasal route [ 17 ]. It may be that a large quantity of ADV is required to induce an adequate immune response in domestic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Although AD does not occur in laboratory animals under natural conditions, they are highly susceptible to experimental infection [ 111 ]. Rabbits were found to be the most sensitive species [ 112 ] and have been used for diagnostic purposes [ 113 ]. When subcutaneously inoculated, rabbits exhibit neurological deficits, hyperactivity, intense pruritus and self-mutilation at the site of inoculation [ 114 ].…”
Section: Aujeszky’s Disease In Mammalsmentioning
confidence: 99%